Barriers to Using Shared Mobility Electric-Scooters in Dubai: The DEMATEL Approach - ALMARRI, HESSA MARWAN (2024)
This study investigates barriers to the widespread adoption of shared mobility electric scooters (e-scooters) in Dubai. Using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method, the research identifies key obstacles such as weather conditions, safety concerns, limited availability, and service coverage. Expert opinions validate the findings, emphasising the need to address these barriers to enhance e-scooter acceptance and usage in the city. Keywords: electronic-scooter, barriers, shared mobility, DEMATEL